Proteomic Changes in the Sound Vibration-Treated Arabidopsis thaliana Facilitates Defense Response during Botrytis cinerea Infection - Ritesh Ghosh; Bosung Choi; Young Sang Kwon; Tufail Bashir; Dong-Won Bae; Hanhong Bae (The Plant Pathology Journal, 2019)
Sound vibration (SV) treatment can trigger various molecular and physiological changes in plants. Previously, we showed that pre-exposure of Arabidopsis plants to SV boosts its defense response against Botrytis cinerea fungus. The present study was aimed to investigate the changes in the proteome states in the SV-treated Arabidopsis during disease progression. Proteomics analysis identified several upregulated proteins in the SV-infected plants (i.e., SV-treated plants carrying Botrytis infection). These upregulated proteins are involved in a plethora of biological functions, e.g., primary metabolism (i.e., glycolysis, tricarboxylic acid cycle, ATP synthesis, cysteine metabolism, and photosynthesis), redox homeostasis, and defense response. Additionally, our enzyme assays confirmed the enhanced activity of antioxidant enzymes in the SV-infected plants compared to control plants. Broadly, our results suggest that SV pre-treatment evokes a more efficient defense response in the SV-infected plants by modulating the primary metabolism and reactive oxygen species scavenging activity.